1986
DOI: 10.1002/jhrc.1240090506
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous assay of serum vitamin A and vitamin E by high performance liquid chromatography using time‐switched UV and fluorimetric detectors

Abstract: SummaryAn HPLC method utilizing a UV and a fluorimetricdetector linked in series is described. By use of a simple integrator-controlled time-switched relay, analysis of serum vitamins A and E is accomplished on the same chromatogram and at optimum sensitivity for each detector. A single internal standard (retinyl acetate) monitored only by the UV detector permits measurement of both vitamins over a wide linear range. Precision of the assays is satisfactory, both on a within-day and on a day-to-day basis. Recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…During With the availability of a series of some 5,000 serum samples from a new prospective breast cancer study on women resident on the island of Guernsey, it seemed appropriate to re-investigate the problem using a newly developed high performance liquid chromatography (HPLC) method which included butylated hydroxytoluene (BHT) as an antioxidant (Russell et al, 1986). In addition, serum retinol binding protein (RPB), which is a good indicator of nutritional status (Gofferje, 1978;Tyler et al, 1984) Serum retinol and a-tocopherol were measured by HPLC (Russell et al, 1986). Several workers (Chow et al, 1983;Driskell et al, 1985) have shown that the addition of antioxidant at the extraction stage of the analysis prevents the loss of vitamin A, even in frozen stored serum samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During With the availability of a series of some 5,000 serum samples from a new prospective breast cancer study on women resident on the island of Guernsey, it seemed appropriate to re-investigate the problem using a newly developed high performance liquid chromatography (HPLC) method which included butylated hydroxytoluene (BHT) as an antioxidant (Russell et al, 1986). In addition, serum retinol binding protein (RPB), which is a good indicator of nutritional status (Gofferje, 1978;Tyler et al, 1984) Serum retinol and a-tocopherol were measured by HPLC (Russell et al, 1986). Several workers (Chow et al, 1983;Driskell et al, 1985) have shown that the addition of antioxidant at the extraction stage of the analysis prevents the loss of vitamin A, even in frozen stored serum samples.…”
Section: Discussionmentioning
confidence: 99%
“…Several workers (Chow et al, 1983;Driskell et al, 1985) have shown that the addition of antioxidant at the extraction stage of the analysis prevents the loss of vitamin A, even in frozen stored serum samples. We have also found that with the addition of BHT, both vitamins A and E are stable, in that there is no significant correlation between time in storage and titre (Russell et al, 1986).The RBP was assayed by the Behring LC-Partigen Immunodiffusion Plate method from Hoechst Pharmaceuticals Ltd., Hounslow, UK. After addition of the serum to each well on the assay plates, they were left for 48 h at room temperature before measurement of the diffusion area.…”
mentioning
confidence: 99%
“…Vitamin E has been little studied in relation to cervix cancer. An inverse relation has been reported in one study (Knekt, 1988) but not another (Heinonen et al, 1987).We have examined serum levels of vitamin A and vitamin E in young women aged Sera were analysed blindly for vitamin A and vitamin E according to the procedure of Russell et al (1986). Antioxidant (BHT) was added prior to extraction to ensure that both vitamins A and E were stable after prolonged storage (Russell et al, 1986).…”
mentioning
confidence: 99%
“…We have examined serum levels of vitamin A and vitamin E in young women aged Sera were analysed blindly for vitamin A and vitamin E according to the procedure of Russell et al (1986). Antioxidant (BHT) was added prior to extraction to ensure that both vitamins A and E were stable after prolonged storage (Russell et al, 1986).…”
mentioning
confidence: 99%
See 1 more Smart Citation